High-performance polymer solid electrolyte based on electron irradiation, preparation method of high-performance polymer solid electrolyte, secondary battery and electric device

Through electron irradiation treatment of polymer solid electrolytes, the ionic conductivity and mechanical properties have been significantly improved, the problem of insufficient electrolyte performance in the existing technology has been solved, and the industrial application of solid-state batteries has been promoted.

CN119400945AInactive Publication Date: 2025-02-07STATE POWER INVESTMENT CORPORATION RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411542492.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polymer solid electrolytes have insufficient ionic conductivity and high voltage compatibility, which cannot meet the requirements of future energy storage systems, hindering its commercialization in lithium battery applications.

Method used

The polymer solid electrolyte is treated by electron irradiation, which significantly improves its ionic conductivity and mechanical properties, and a high-performance polymer solid electrolyte is prepared.

Benefits of technology

It improves the ionic conductivity and mechanical properties of polymer solid electrolytes, solves its key problems in the industrial application of solid-state batteries, and promotes the mass production and application of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400945A_ABST
    Figure CN119400945A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance polymer solid electrolyte based on electron irradiation, a preparation method of the high-performance polymer solid electrolyte, a secondary battery and an electric device. The high-performance polymer solid electrolyte is prepared through electron irradiation, the ionic conductivity of the high-performance polymer solid electrolyte is remarkably improved, the mechanical performance of the high-performance polymer solid electrolyte is optimized, and the key principle problem of the high-performance polymer solid electrolyte in solid-state battery industrial application is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a high-performance polymer solid-state electrolyte based on electron irradiation, a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries are crucial to electric vehicles, energy storage and other fields. As the capacity of lithium-ion batteries increases, their energy density bottleneck and safety issues become more prominent. Solid-state batteries have higher theoretical energy density and greatly improved safety performance, and are one of the development directions of the next generation of lithium-ion batteries.

[0003] Polymer solid electrolytes such as polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyphenylene ether (PPO) and polyethylene oxide (PEO) have excellent mechanical processing properties, good flexibility, easy construction of solid-solid interface, and can be used to prepare large-capacity batteries. Therefore, they are widely used in the development of all-solid-state lithium-ion batteries. However, the ionic conductivity (10 -6 ~10 -5 S cm -1 ) and high-voltage compatibility still cannot meet the requirements of future energy storage systems, and these problems seriously hinder its further commercialization in future lithium battery applications. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] To this end, embodiments of the present invention provide a high-performance polymer solid electrolyte based on electron irradiation, a preparation method thereof, a secondary battery, and an electrical device.

[0006] In a first aspect, the present invention proposes a high-performance polymer solid electrolyte based on electron irradiation, wherein the high-performance polymer solid electrolyte is obtained by subjecting a polymer solid electrolyte to electron irradiation treatment in situ.

[0007] Among them, the polymer solid electrolyte is the solid electrolyte before irradiation, and the high-performance polymer solid electrolyte is the solid electrolyte after irradiation.

[0008] Furthermore, the polymer solid electrolyte includes at least one of PAN, PMMA, PPO, PEO and derivatives thereof.

[0009] Among them, derivatives refer to substances with a certain degree of doping optimization obtained by adding inorganic fillers or electrolyte salts to polymer solid electrolytes PAN, PMMA, PPO or PEO. Inorganic fillers include oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, sulfur oxide solid electrolytes, halogen oxide solid electrolytes and composite solid electrolytes; electrolyte salts include lithium-containing inorganic salts, lithium-containing organic salts, sodium-containing inorganic salts, sodium-containing organic salts and multi-salt complexes.

[0010] The present invention does not change the components of the polymer solid electrolyte, but performs electron irradiation treatment on the polymer solid electrolyte in situ to obtain a uniform high-performance polymer solid electrolyte. Compared with the original polymer solid electrolyte, the high-performance polymer solid electrolyte prepared by this method has significantly improved ion conductivity and mechanical properties.

[0011] In a second aspect, the present invention provides a method for preparing a high-performance polymer solid electrolyte based on electron irradiation as provided in the first aspect, comprising the following steps:

[0012] (a) selecting a polymer solid electrolyte, wherein the polymer solid electrolyte includes a single-layer polymer solid electrolyte sheet and a multi-layer polymer solid electrolyte sheet group stacked in sequence;

[0013] (b) starting an electron irradiation device to perform electron irradiation on the polymer solid electrolyte.

[0014] The polymer solid electrolyte in step (a) can be a single-layer polymer solid electrolyte sheet, or a plurality of layers of polymer solid electrolyte sheets stacked together. That is, the present invention can irradiate multiple layers of polymer solid electrolyte sheets at one time after stacking them, thereby simplifying the process and saving energy.

[0015] Electron irradiation equipment is a device that uses high-energy electron beams to irradiate materials to improve material properties. Electron irradiation equipment includes medium-energy electron accelerators (denami type, insulation core transformer type, high-pressure high-voltage transformer type, resonant transformer type, etc.) and high-energy electron accelerators (linear type, etc.).

[0016] Further, the thickness of the polymer solid electrolyte is less than 2 cm. It is understandable that when the polymer electrolyte is a single-layer polymer electrolyte sheet, the thickness of the single-layer polymer electrolyte sheet is less than 2 cm, and when the polymer electrolyte is a multi-layer polymer solid electrolyte sheet group stacked up and down, the thickness of the polymer solid electrolyte sheet group is less than 2 cm.

[0017] Furthermore, in the step (b), the irradiation temperature of the electron irradiation equipment is 25-200°C.

[0018] When the irradiation temperature is 25°C, the electron irradiation is carried out at room temperature. Irradiation at a suitable irradiation temperature can improve the irradiation efficiency and economy. Too high an irradiation temperature will cause negative cross-linking of the polymer and increase the process cost by increasing the temperature. Too low an irradiation temperature may reduce the irradiation effect and increase the process cost by decreasing the temperature.

[0019] In some embodiments, the irradiation temperature is room temperature (25° C.), 50° C., 80° C., 100° C., 130° C., 150° C., 180° C., 200° C., or a value within a range consisting of any two of these values.

[0020] Furthermore, the electron energy of the electron irradiation equipment in step (b) is 120keV to 10MeV.

[0021] Irradiation under appropriate electron energy conditions can obtain appropriate irradiation effects and improve irradiation efficiency and economy. Too high electron energy may cause negative cross-linking and increase equipment costs. Too low electron energy may cause insufficient penetration depth of the electron beam, which may result in insufficient irradiation or low irradiation efficiency.

[0022] In some embodiments, the electron energy is 120keV, 200keV, 300keV, 400keV, 500keV, 600keV, 700keV, 800keV, 900keV, 1MeV, 2MeV, 3MeV, 4MeV, 5MeV, 6MeV, 7MeV, 8MeV, 9MeV, 10MeV, or a value in a range consisting of any two of the values.

[0023] Furthermore, in the step (b), the electron current intensity of the electron irradiation equipment is 0.1 to 1000 mA.

[0024] Irradiation under appropriate electron current intensity conditions can obtain appropriate irradiation effects and improve irradiation efficiency. Too high electron current intensity may produce too strong thermal effect in the solid electrolyte, while too low electron current intensity may result in too low irradiation efficiency and too long irradiation time.

[0025] In some embodiments, the electron current intensity is 0.1 mA, 0.5 mA, 1 mA, 5 mA, 10 mA, 30 mA, 50 mA, 60 mA, 80 mA, 100 mA, 200 mA, 400 mA, 500 mA, 700 mA, 900 mA, 1000 mA, or a value in a range consisting of any two values.

[0026] Furthermore, in the step (b), the electron irradiation dose of the electron irradiation equipment is 0.1 to 100 kGy.

[0027] Irradiation under appropriate electron irradiation dose conditions can obtain appropriate irradiation effects and improve economic efficiency. Too high an electron irradiation dose may cause negative cross-linking and increase process costs, while too low an electron irradiation dose may result in insufficient irradiation effects.

[0028] In some embodiments, the electron irradiation dose is a value within a range consisting of any two of 0.1 kGy, 0.5 kGy, 0.9 kGy, 1 kGy, 3 kGy, 5 kGy, 8 kGy, 10 kGy, 20 kGy, 30 kGy, 40 kGy, 50 kGy, 60 kGy, 70 kGy, 80 kGy, 90 kGy, and 100 kGy.

[0029] In a third aspect, the present invention provides a secondary battery comprising the high-performance polymer solid electrolyte proposed in the first aspect or the high-performance polymer solid electrolyte prepared by the method proposed in the second aspect.

[0030] In a fourth aspect, the present invention provides an electrical device comprising the secondary battery provided in the third aspect.

[0031] Compared with the prior art, the beneficial effects of the present invention are:

[0032] The present invention prepares a high-performance polymer solid electrolyte through electron irradiation, the ionic conductivity of which is significantly improved, and the mechanical properties are optimized, so that the key fundamental problems faced by the polymer solid electrolyte in the industrial application of solid-state batteries are improved.

[0033] The method of the present invention does not change the original polymer solid electrolyte structure and components, has a simple process and low cost, and the prepared high-performance polymer solid electrolyte is stable and reliable. It is expected to provide a solution for the industrial application of solid-state batteries and promote the mass production and application of all-solid-state batteries in new energy vehicles, drones, mobile electronic devices, energy storage and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0035] Figure 1 The present invention is a flow chart of the preparation method of high-performance polymer solid electrolyte based on electron irradiation. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0037] Please refer to the attached Figure 1 The present invention is specifically described in combination with the following examples and comparative examples. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0038] Example 1

[0039] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0040] At room temperature, the solid electrolyte sheet PEO-1 was obtained by irradiation treatment under the conditions of electron energy of 120keV, electron current of 50mA and electron irradiation dose of 5kGy.

[0041] Example 2

[0042] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0043] At room temperature, the solid electrolyte sheet PEO-2 was obtained by irradiation treatment under the conditions of electron energy of 800keV, electron current of 50mA and electron irradiation dose of 5kGy.

[0044] Example 3

[0045] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0046] At room temperature, the solid electrolyte sheet PEO-3 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current intensity 50mA and electron irradiation dose 5kGy.

[0047] Example 4

[0048] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0049] At room temperature, the solid electrolyte sheet PEO-4 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current intensity 50mA and electron irradiation dose 5kGy.

[0050] Example 5

[0051] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0052] At room temperature, the solid electrolyte sheet PEO-5 was obtained by irradiation treatment under the conditions of electron energy 8MeV, electron current intensity 50mA and electron irradiation dose 5kGy.

[0053] Example 6

[0054] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0055] At room temperature, the solid electrolyte sheet PEO-6 was obtained by irradiation treatment under the conditions of electron energy of 10 MeV, electron current of 50 mA and electron irradiation dose of 5 kGy.

[0056] Example 7

[0057] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0058] At room temperature, the solid electrolyte sheet PMMA-7 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current intensity 0.1mA and electron irradiation dose 5kGy.

[0059] Example 8

[0060] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0061] At room temperature, the solid electrolyte sheet PMMA-8 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current intensity 10mA and electron irradiation dose 5kGy.

[0062] Example 9

[0063] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0064] At room temperature, the solid electrolyte sheet PMMA-9 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current 60mA and electron irradiation dose 5kGy.

[0065] Example 10

[0066] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0067] At room temperature, the solid electrolyte sheet PMMA-10 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current 200mA and electron irradiation dose 5kGy.

[0068] Embodiment 11

[0069] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0070] At room temperature, the solid electrolyte sheet PMMA-11 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current 500mA and electron irradiation dose 5kGy.

[0071] Example 12

[0072] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0073] At room temperature, the solid electrolyte sheet PMMA-12 was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current intensity 700mA and electron irradiation dose 5kGy.

[0074] Example 13

[0075] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0076] At room temperature, the solid electrolyte sheet PMMA-13 ​​was obtained by irradiation treatment under the conditions of electron energy 2MeV, electron current intensity 1000mA and electron irradiation dose 5kGy.

[0077] Embodiment 14

[0078] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0079] At room temperature, the solid electrolyte sheet PPO-14 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current intensity 500mA and electron irradiation dose 0.1kGy.

[0080] Embodiment 15

[0081] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0082] At room temperature, the solid electrolyte sheet PPO-15 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current 500mA and electron irradiation dose 1kGy.

[0083] Example 16

[0084] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0085] At room temperature, the solid electrolyte sheet PPO-16 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current intensity 500mA and electron irradiation dose 8kGy.

[0086] Embodiment 17

[0087] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0088] At room temperature, the solid electrolyte sheet PPO-17 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current intensity 500mA and electron irradiation dose 50kGy.

[0089] Embodiment 18

[0090] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0091] The solid electrolyte sheet PPO-18 was obtained by irradiation treatment under the conditions of electron energy of 5MeV, electron current of 500mA and electron irradiation dose of 100kGy at room temperature.

[0092] Embodiment 19

[0093] A solid electrolyte sheet PAN with a single layer thickness of 1 mm was selected;

[0094] At room temperature, the solid electrolyte sheet PAN-19 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current intensity 50mA and electron irradiation dose 50kGy.

[0095] Embodiment 20

[0096] The irradiated solid electrolyte sheet PAN-20 was obtained by irradiating the solid electrolyte sheet at 50° C., with an electron energy of 5 MeV, an electron current of 50 mA, and an electron irradiation dose of 50 kGy.

[0097] Embodiment 21

[0098] The irradiated solid electrolyte sheet PAN-21 was obtained by irradiating the solid electrolyte sheet at 70°C, with an electron energy of 5MeV, an electron current of 50mA and an electron irradiation dose of 50kGy.

[0099] Embodiment 22

[0100] The irradiated solid electrolyte sheet PAN-22 was obtained by irradiating the substrate at 100° C., with an electron energy of 5 MeV, an electron current of 50 mA, and an electron irradiation dose of 50 kGy.

[0101] Embodiment 23

[0102] The irradiated solid electrolyte sheet PAN-23 was obtained by irradiation treatment at 140° C., with an electron energy of 5 MeV, an electron current of 50 mA, and an electron irradiation dose of 50 kGy.

[0103] Embodiment 24

[0104] The irradiated solid electrolyte sheet PAN-24 was obtained by irradiating the substrate at 200° C., with an electron energy of 5 MeV, an electron current of 50 mA, and an electron irradiation dose of 50 kGy.

[0105] Embodiment 25

[0106] A solid electrolyte sheet group PEO with a total thickness of 3 mm is selected, wherein the thickness of a single layer of the solid electrolyte sheet PEO is 1 mm;

[0107] At room temperature, the solid electrolyte sheet PEO-25 was obtained by irradiation treatment under the conditions of electron energy of 800keV, electron current of 50mA and electron irradiation dose of 60kGy.

[0108] Embodiment 26

[0109] A solid electrolyte sheet group PEO with a total thickness of 10 mm is selected, wherein the thickness of a single layer of the solid electrolyte sheet PEO is 1 mm;

[0110] At room temperature, the solid electrolyte sheet PEO-26 was obtained by irradiation treatment under the conditions of electron energy of 800keV, electron current of 50mA and electron irradiation dose of 60kGy.

[0111] Embodiment 27

[0112] A solid electrolyte sheet group PEO with 20 layers stacked together and a total thickness of 20 mm is selected, wherein the thickness of a single layer of the solid electrolyte sheet PEO is 1 mm;

[0113] At room temperature, the solid electrolyte sheet PEO-27 was obtained by irradiation treatment under the conditions of electron energy of 800keV, electron current of 50mA and electron irradiation dose of 60kGy.

[0114] Comparative Example 1

[0115] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0116] The irradiated solid electrolyte sheet D-PMMA-1 was obtained by irradiating the solid electrolyte sheet D-PMMA-1 at room temperature with an electron energy of 2MeV, an electron current of 0.001mA and an electron irradiation dose of 5kGy.

[0117] Comparative Example 2

[0118] Select a solid electrolyte sheet PMMA with a single layer thickness of 1 mm;

[0119] The irradiated solid electrolyte sheet D-PMMA-2 was obtained by irradiating the solid electrolyte sheet under the conditions of electron energy 2MeV, electron current intensity 10000mA and electron irradiation dose 5kGy at room temperature.

[0120] Comparative Example 3

[0121] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0122] The solid electrolyte sheet D-PEO-3 was obtained by irradiation treatment under the conditions of electron energy 1keV, electron current 500mA and electron irradiation dose 5kGy at room temperature.

[0123] Comparative Example 4

[0124] A solid electrolyte sheet PEO with a single layer thickness of 1 mm was selected;

[0125] At room temperature, the irradiation treatment was carried out under the conditions of electron energy of 50 MeV, electron current of 500 mA and electron irradiation dose of 5 kGy to obtain the irradiated solid electrolyte sheet D-PEO-4.

[0126] Comparative Example 5

[0127] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0128] At room temperature, the irradiation treatment was carried out under the conditions of electron energy of 5 MeV, electron current of 500 mA and electron irradiation dose of 0.001 kGy to obtain the irradiated solid electrolyte sheet D-PPO-5.

[0129] Comparative Example 6

[0130] A solid electrolyte sheet PPO with a single layer thickness of 1 mm was selected;

[0131] The solid electrolyte sheet D-PPO-6 was obtained by irradiation treatment under the conditions of electron energy 5MeV, electron current 500mA and electron irradiation dose 1000kGy at room temperature.

[0132] Comparative Example 7

[0133] A solid electrolyte sheet PAN with a single layer thickness of 1 mm was selected;

[0134] The irradiated solid electrolyte sheet D-PAN-7 was obtained by irradiation treatment at -10°C, electron energy 5MeV, electron current 500mA, and electron irradiation dose 50kGy.

[0135] Comparative Example 8

[0136] A solid electrolyte sheet PAN with a single layer thickness of 1 mm was selected;

[0137] The irradiated film was irradiated at 500° C., with an electron energy of 5 MeV, an electron current of 500 mA, and an electron irradiation dose of 50 kGy to obtain a solid electrolyte sheet D-PAN-8 after irradiation.

[0138] Comparative Example 9

[0139] A solid electrolyte sheet group with 28 layers stacked up to a total thickness of 28 mm is selected, wherein the solid electrolyte sheets include 7 layers of solid electrolyte sheets PEO with a single thickness of 1 mm, 7 layers of solid electrolyte sheets PMMA with a single thickness of 1 mm, 7 layers of solid electrolyte sheets PPO with a single thickness of 1 mm, and 7 layers of solid electrolyte sheets PAN with a single thickness of 1 mm, and the stacking method is stacking in sequence;

[0140] At room temperature, the irradiation treatment was carried out under the conditions of electron energy of 800keV, electron current of 500mA and electron irradiation dose of 60kGy to obtain irradiated solid electrolyte sheets D-PEO-9, D-PMMA-9, D-PPO-9 and D-PAN-9.

[0141] Test Example 1

[0142] Solid-state batteries were prepared using solid electrolytes that had not been subjected to electron irradiation treatment, and solid electrolytes that had been subjected to electron irradiation treatment prepared in Examples 1 to 27 and Comparative Examples 1 to 9, and their ionic conductivities were tested.

[0143] Among them, the preparation process of the solid-state battery is as follows: the preparation of the positive electrode sheet is to first put the active material (LiFePO4), Ketjen black and polymer binder (PVDF) into a mortar at a mass ratio of 8:1:1 and grind them thoroughly. After grinding, they are dispersed in an appropriate amount of N-methylpyrrolidone (NMP). After adjusting to a suitable viscosity, they are stirred on a magnetic stirrer for 12 hours to make a positive electrode slurry. The slurry after stirring for 12 hours is scraped with a spoon on the surface of a rectangular aluminum foil washed with anhydrous ethanol, coated with a coater, and then placed in an 80°C forced air drying oven for 24 hours to obtain a LiFePO4 positive electrode. The positive electrode material is cut into discs with a 12mm diameter punching machine, and the loading amount is about 2.5mg / cm 2 Finally, the LiFePO4 / solid polymer electrolyte membrane / Li CR 2032 button cell was assembled in a glove box filled with argon atmosphere and placed in a 65°C oven overnight for testing to enhance the contact between the solid polymer electrolyte membrane and the electrode. The solid polymer battery was electrochemically tested using a NEWARE battery test cabinet with a cutoff voltage of 2.5-4.0V. The rate in the charge and discharge cycle test was based on 1C = 174mAh / g.

[0144] The test method of ionic conductivity is as follows: In order to test the conductivity of the electrolyte membrane, stainless steel (Fe) is first used as a blocking electrode to assemble a symmetrical battery of Fe|electrolyte membrane|Fe, and the battery shell is a 2032 battery shell. After assembly, the test battery is placed in a constant temperature and humidity chamber and tested at the set temperature (25°C). The Shanghai Chenhua electrochemical workstation CHI760E is used for AC impedance testing with a frequency range of 0.1Hz to 1MHz, an amplitude of 0.05V, a standing time of 2 seconds, and an open circuit voltage set according to the actual value. The impedance value in the high-frequency region is fitted by the Nyquist diagram, combined with the thickness and area of ​​the electrolyte membrane, and the formula is used. Calculate the conductivity. Where: σ is the ionic conductivity, in Siemens per centimeter (S cm -1); d is the thickness of the electrolyte membrane measured after the EIS test, in centimeters (cm); Re is the total resistance of charge transfer recorded by the EIS test, in ohms (Ω); S is the actual contact area between stainless steel (Fe) and the solid polymer electrolyte membrane, that is, the area of ​​the SS spacer layer (1.89 cm 2 ).

[0145] Mechanical properties tests were performed on solid electrolytes that were not subjected to electron irradiation treatment, and solid electrolytes that were subjected to electron irradiation treatment prepared in Examples 1 to 28 and Comparative Examples 1 to 9. Among them, the method of mechanical properties testing is: first, the sample is cut into membranes with a width of 10 mm to ensure that the surface is flat and defect-free. Use a universal material testing machine and set the test conditions: the temperature is room temperature, the test speed is 50 mm / min, and the distance between the clamps is 100 mm. When installing the clamps, ensure that the sample is fixed tightly and evenly. After starting the testing machine, a tensile test is performed, and the changes in the tensile load and sample length are recorded to monitor the mechanical properties of the sample in real time.

[0146] The test results are shown in Table 1 below.

[0147] Table 1:

[0148]

[0149]

[0150]

[0151] According to Examples 1 to 27, compared with before irradiation, the ionic conductivity and mechanical properties of the solid electrolytes PEO, PMMA, PPO, and PAN are significantly improved after irradiation.

[0152] By comparing Examples 7 to 13 and Comparative Examples 1 and 2, it can be seen that when the electron current intensity is too high or too low, the ionic conductivity of D-PMMA-1 and D-PMMA-2 after irradiation is improved, but the mechanical properties are not significantly improved.

[0153] By comparing Examples 1 to 6, Comparative Examples 3 and 4, it can be seen that when the electron energy is too high or too low, the ionic conductivity and mechanical properties of D-PEO-3 and D-PEO-4 after irradiation are not significantly improved.

[0154] By comparing Examples 14 to 18, Comparative Example 5 and Comparative Example 6, it can be seen that when the electron irradiation dose is too low, the ionic conductivity and mechanical properties of the irradiated D-PPO-5 are not improved, and when the electron irradiation dose is too high, the ionic conductivity and mechanical properties of the irradiated D-PPO-6 are improved, but not significantly.

[0155] By comparing Examples 19 to 24, Comparative Examples 7 and 8, it can be seen that when the irradiation temperature is too low or too high, the ionic conductivity of D-PAN-7 and D-PAN-8 after irradiation is not significantly improved, and when the irradiation temperature is too high, the mechanical properties of D-PAN-8 after irradiation are reduced.

[0156] By comparing Examples 1 to 6, Examples 25 to 27 and Comparative Example 9, it can be seen that within the thickness range of 2 cm, the ionic conductivity and mechanical properties of the solid electrolyte after single-layer irradiation and multi-layer superimposed irradiation are significantly improved. When the thickness is too large, the ionic conductivity and mechanical properties of the solid electrolyte after irradiation are not significantly improved.

[0157] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0158] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0159] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A high-performance polymer solid electrolyte based on electron irradiation, characterized in that: The high-performance polymer solid electrolyte is obtained by in-situ electron irradiation treatment of the polymer solid electrolyte.

2. The high-performance polymer solid electrolyte based on electron irradiation according to claim 1, characterized in that: The polymer solid electrolyte includes at least one of PAN, PMMA, PPO, PEO and derivatives thereof.

3. A method for preparing a high-performance polymer solid electrolyte based on electron irradiation, characterized in that: The method for preparing the high-performance polymer solid electrolyte as claimed in claim 1 or 2 comprises the following steps: (a) selecting a polymer solid electrolyte, wherein the polymer solid electrolyte includes a single-layer polymer solid electrolyte sheet and a multi-layer polymer solid electrolyte sheet group stacked in sequence; (b) starting an electron irradiation device to perform electron irradiation on the polymer solid electrolyte.

4. The method according to claim 3, characterized in that The thickness of the polymer solid electrolyte is less than 2 cm.

5. The method according to claim 3, characterized in that The irradiation temperature of the electron irradiation equipment in the step (b) is 25-200°C.

6. The method according to claim 3, characterized in that The electron energy of the electron irradiation equipment in step (b) is 120keV to 10MeV.

7. The method according to claim 3, characterized in that The electron current intensity of the electron irradiation equipment in the step (b) is 0.1-1000 mA.

8. The method according to claim 3, characterized in that The electron irradiation dose of the electron irradiation equipment in the step (b) is 0.1 to 100 kGy.

9. A secondary battery, characterized in that: The invention comprises the high performance polymer solid electrolyte as claimed in claim 1 or 2 or the high performance polymer solid electrolyte prepared by the method as claimed in any one of claims 3 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method of high-performance polymer electrolyte

    CN116666746A

  • Method for manufacturing an electrochemical cell having a separator membrane for separation of electrodes in the electrochemical cell and a device thereof

    US20230022742A1